PENGARUH PENYULUHAN TENTANG SADARI TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI DI PPP. AN NAJIYAH BAHRUL ‘ULUM TAMBAKBERAS JOMBANG - Rozi, Fahrur; Kurniawan, Vendi Eko; Munfaati, Rukmana (WELL BEING, 2018)
Breast cancer is the second leading cause of cancer death in women after cervical cancer. Failure to detect breast cancer early can occur due to lack of knowledge gained by the community. The purpose of this research is to know the influence of advising about the awareness of knowledge and attitude of adolescent woman in PP. Putri a NajiyahBahrul 'UlumTambakberasJombang. The design of this study was pre-experimental. The samples used in this study were 45 respondents with random sampling technique by distributing questionnaires. Based on the results of research before the advising, knowledge of respondents almost all have less knowledge that is 38 respondents (84.4%) and attitudes of respondents almost all have a negative attitude that is 36 respondents (80%). After doing the advising, all respondents have good knowledge that is 100% and attitude of respondent mostly have positive attitude that is 25 respondents (55, 6%) Data analysis using Wilcoxon test statistic test show significance value before and after α = 0,000, attitude before and after α = 0,002 (α> 0, 05) means H1 is accepted then there is influence of advising to level of knowledge and attitude of young woman. Furthermore, it is necessary to monitor about health inspection to health officer around Pesantren.